2020
DOI: 10.1177/1357633x20959213
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes consultation versus diabetes education in patients with poor glycaemic control: A telemedicine intervention study

Abstract: Introduction The prevalence of diabetes is increasing around the world, especially in populations with limited health service resources. Diabetes is associated with increased mortality and cost. Therefore, we investigated the impact of increasing access to diabetes care through telemedicine. Methods Five rural communities were connected via videoconference. Patients received diabetes consultation (DC) or diabetes self-management education (DSME). DC was performed by an endocrinologist, while DSME was delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“… Majithia et al 17 2020 Pre-post 55 DM 4 months Video consult, mobile application, remote consult, connected BGMs and CGMs HbA1c, blood glucose levels, BP, TC, HDL-C, TC/HDL ratio, LDL-C, TG Significant improvements in LDL-C, TC/HDL ratio, TG, HbA1c, BMI, and SBP in telehealth group. Nyenwe et al 59 2020 Pre-post 69 DM 36 months Video consult HbA1c, BP, lipid profile No significant difference in lipid levels between groups. Telehealth group improved glycemic control.…”
Section: Resultsmentioning
confidence: 94%
“… Majithia et al 17 2020 Pre-post 55 DM 4 months Video consult, mobile application, remote consult, connected BGMs and CGMs HbA1c, blood glucose levels, BP, TC, HDL-C, TC/HDL ratio, LDL-C, TG Significant improvements in LDL-C, TC/HDL ratio, TG, HbA1c, BMI, and SBP in telehealth group. Nyenwe et al 59 2020 Pre-post 69 DM 36 months Video consult HbA1c, BP, lipid profile No significant difference in lipid levels between groups. Telehealth group improved glycemic control.…”
Section: Resultsmentioning
confidence: 94%
“…In an Advanced Chronic Kidney Disease Study, interventions to lower HbA1c levels did not affect cognitive decline ( 41 ). However, a Diabetes Education and Telemedicine Study (IDEATel) demonstrated that cognitive decline was observed with interventions at HbA1c <7.0% ( 42 ). In this study, the higher the HbA1c level, the more likely the patient was to develop MCI, indicating a bidirectional relationship between cognitive impairment and diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…They often work as part of a care team to help those with diabetes understand their disease and achieve their goals in managing diabetes. A recent study found that glycemic and metabolic outcomes were similar in patients who received a telehealth-based diabetes consultation with an endocrinologist or a diabetes self-management education visit with a CDCES [5]. Because CDCESs train patients who are new to CGM, their comfort with CGM device insertion and app setup is also critical to patient training and adoption.…”
Section: Introductionmentioning
confidence: 99%